PROXIMATE AND ULTIMATE ANALYSIS OF FUEL PELLETS FROM OIL PALM RESIDUES (Nigerian Journal of Technology, 2017)
This study carried out an investigation on the proximate and ultimate analysis of fuel pellets from oil palm residues such as palm kernel shell, PKS, palm fibre, PF and empty fruit bunch, EFB using the ASTM standards. The results obtained were compared. The percentage moisture content of the pellets, PKS, PF and EFB were 9.68%, 10.77%, 12.07% respectively. This is significantly lower than the percentage moisture content of the raw residues given as 10.23%, 11.10% and 15.01% respectively. High volatile matter content in the fuel pellets indicates that there would be ease of ignition during combustion. The results also show that the pellets have a lower ash content of 0.69%, 3.69% and 3.72% as against that of the raw residues, which is 3.24%, 7.90% and 4.48% respectively. There was really no significant reduction in emission of sulphur gases between the fuel pellets and the raw residues except for the Palm Fibre, PF, pellets and raw residues that varies. Essentially, from the general results obtained from the analysis, it can be deduced that pellets are more suitable for boilers in steam power plants.  http://dx.doi.org/10.4314/njt.v36i3.44